2017
DOI: 10.5194/acp-17-439-2017
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of air pollution and climate on materials in Athens, Greece

Abstract: Abstract. For more than 10 years now the National and Kapodistrian University of Athens, Greece, has contributed to the UNECE (United Nations Economic Commission for Europe) ICP Materials (International Co-operative Programme on Effects on Materials including Historic and Cultural Monuments) programme for monitoring the corrosion/soiling levels of different kinds of materials due to environmental air-quality parameters. In this paper we present the results obtained from the analysis of observational data that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…In this section are presented the estimates obtained by implementing previous mentioned analysis, referred to as "Satellite based", along with experimental deterioration data collected during one year exposures, the periods October to September of the years 2005-2006, 2008-2009, 2011-2012 and 2014-2015 at Athens, Greece, referred to as "Observed", and the estimates of Eqs 1, 2 and 3 using ground based data, referred to as "Ground based". The procedure involved in the experimental determination of the observed deterioration values has already been published 38 . In that work are also included the results from all the experimental exposure periods and ground based estimates shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section are presented the estimates obtained by implementing previous mentioned analysis, referred to as "Satellite based", along with experimental deterioration data collected during one year exposures, the periods October to September of the years 2005-2006, 2008-2009, 2011-2012 and 2014-2015 at Athens, Greece, referred to as "Observed", and the estimates of Eqs 1, 2 and 3 using ground based data, referred to as "Ground based". The procedure involved in the experimental determination of the observed deterioration values has already been published 38 . In that work are also included the results from all the experimental exposure periods and ground based estimates shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…For individual materials, their DRFs are developed involving the air pollutants and climatic parameters which affect the particular material. The development of these functions is based on corrosion/soiling experiments made under laboratory conditions but also in the real environment [36][37][38] . In this preliminary study, we use part of the available DRFs and specifically the ones for the materials carbon steel, zinc, limestone and modern glass, developed in the framework of the project "International Co-operative Programme on Effects on Materials including Historic and Cultural Monuments (ICP Materials)".…”
Section: Introductionmentioning
confidence: 99%
“…Since the end of 2002, a specialized corrosion station has been installed in Athens, Greece to investigate the corrosion and soiling of many different materials due to environmental factors such as temperature and humidity, as well as due to air pollution [18,19,[78][79][80][81]. Figure 1 shows a part of the station's exposure facilities and Table 2 provides some information on the location of the Atmospheric Corrosion Athens Station (ACAS).…”
Section: Atmospheric Corrosion Athens Station (Acas)mentioning
confidence: 99%
“…As an application of the satellite data studied in the AQ-China project, they were used in studies on the effects of air pollution and other environmental parameters on materials at the National and Kapodistrian University of Athens [19,48]. The results from this study are briefly reported in this paper as a part of the AEROSOL sub-project.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding vegetation, O 3 can damage plant leaves (decreases in both leaf photosynthesis and leaf area), reducing crop yields associated with a high negative economic impact [11][12][13]. Moreover, as a strong oxidant, it is responsible for the degradation of material via corrosion [14].…”
Section: Introductionmentioning
confidence: 99%